2003
DOI: 10.1539/joh.45.202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stress Management Program for Teachers in Japan: A Pilot Study

Abstract: in enhancing coping skills, increasing social support, and reducing stress responses. Stress management intervention studies in the workplace have increased during the past two decades [1][2][3][4][5][6][7][8][9][10][11][12][13] . It is often assumed that there are two basic approaches to interventions in the workplace 1,9,10) . One is an organization-oriented approach, which aims to identify and improve a stressful work environment, and the other is individual-oriented and aims to enhance the coping abilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 15 publications
2
32
0
Order By: Relevance
“…Thus, the program raised the awareness of the participants and reduced the specific work-related stressors more than lowering general stress. These findings extend those reported by Shimazu et al 36) for 24 teachers in Japan, in which a five-session program combining CB and relaxation training over two weeks was reported to have been ineffective at reducing general stress responses in the intervention compared to the control group. The study measured stress responses including vigour, anger, fatigue, anxiety, depression, and somatic stress responses.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, the program raised the awareness of the participants and reduced the specific work-related stressors more than lowering general stress. These findings extend those reported by Shimazu et al 36) for 24 teachers in Japan, in which a five-session program combining CB and relaxation training over two weeks was reported to have been ineffective at reducing general stress responses in the intervention compared to the control group. The study measured stress responses including vigour, anger, fatigue, anxiety, depression, and somatic stress responses.…”
Section: Discussionsupporting
confidence: 87%
“…[1,2,3]. As a result, teachers may suffer mental and physical health problems due to the variety of job functions and frequent overtime work [4,5]. Many overseas studies showed that teachers were subjected to heavy occupational stress that could adversely affect their mental health status [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, several cognitive-behavioral interventions focusing on improving workers' coping skills have recently been conducted. Findings from these studies suggest that enhancing positive, active, and problem-focused coping skills associated with high job stressors may be a key factor for reducing the negative effects of job stressors and psychological distress of workers 16,17) . Although the buffering effect of coping skills with respect to the relationship between working hours and psychological health is unclear, we assume that appropriate coping skills can affect this relationship.…”
mentioning
confidence: 98%